Supporting Safe-by-Design of Multicomponent Nanomaterials by Linking Functionality-Related Properties with Potential Safety Issues - Swart, Elmer; Westerdiep, Jan-Harm; Badetti, Elena; Brunelli, Andrea; Cazzagon, Virginia; Fernandes, Teresa; Gielen, Anniek M. C; Hristozov, Danail; van Kesteren, Petra C. E.; Krans, Nynke A.; Ouhajji, Samia; Peijnenburg, Willie J. G. M.; Rauscher, Hubert; Soeteman-Hernández, Lya G.; Stone, Vicki; Tsiliki, Georgia; Oomen, Agnes G. (Sustainability & Circularity NOW, 2025)
Advanced materials, including multicomponent nanomaterials (MCNMs), are rationally designed to show specific new or enhanced functionalities. They are considered key in solving current societal challenges, such as the energy transition, yet they represent a challenge themselves to safe innovation and risk assessment. One challenge is the lack of available toxicological information at early innovation stages. Instead, information on functionality and related material properties is generally available at these early innovation stages, but such information is typically not used in safety assessments. Safe-by-Design (SbD) aims to improve the safety of materials and products by integrating safety considerations with functionality as early as possible in the innovation process. To exploit the information on functionality for SbD purposes, a conceptual approach is presented that uses functionality-related material properties to flag potential impacts on risks and guide SbD. This approach relies on insights into relations between material properties and their potential impact on release, fate/toxicokinetics, and toxicity. These relations have been illustrated for 21 new or enhanced material properties that are incorporated in the design of MCNMs. For example, a set of “mechanical properties” was identified as likely to have an impact on release and fate/toxicokinetics of MCNMs, while “reactive properties” were expected to be able to affect their toxicity. The applicability of this approach was briefly explored through several case studies. The presented approach is designed to “flag” potential aspects of risk that require further consideration. These identified aspects can then support the application of SbD for MCNMs, including grouping of similar MCNMs to enable sharing of safety information. The approach is relevant at early stages in the innovation process, where toxicological information is still mostly absent.
Keywords: Material properties; Safe-and-sustainable-by-design; Safe innovation; Risk; Physicochemical properties; Advanced materials